Tender triumph - McNaught, Judith (New York : Pocket Star Books, 1983)
On Friday, a sensuous stranger enters Katie$1 (Bs life. By Sunday, her life is irrevocably changed forever. Katie Connelly submerges her painful past in a promising career, an elegant apartment, and uncomplicated, commitment-free romantic liaisons. Yet something vital is missing from her life and she$1 (Bs uncertain what it is$1 (Buntil she meets proud, rugged Ramon Galverra. With his charm and passionate nature, Ramon gives her a love she has never known. She is still, however, afraid to surrender her heart to this strong, willful, secretive man$1 (Ba man from a different world, a man with a daring, uncertain future.s
Keywords: ROMANCE -- LOVE STORIES